Serie especial: La transición desde la delincuencia juvenil a la delincuencia adulta V - C. Howell, James (Revista Española de Investigación Criminológica, 2015)
This work is the fifth monograph in the special series on Transition from juvenile delinquency to adult crime. The first issue (on criminal transition) was published in the number 9 (2011) of the same journal; the second (about criminal career patterns) and the third (theoretical explanations of criminal transitions) were published in the number 11 (2013), and the forth just in the present 13 number of the journal. Meanwhile, this paper deals with juvenile delinquency in the United States and the combined intervention with juvenile offenders of both justice systems juvenile and adult. The legal debates and the historical circumstances that led youth delinquents to be transferred, in certain cases, to the adult justice system are analysed as well as their problems. Finally, various research results and other rational considerations are reviewed (about brain maturation and individuals? development, effective rehabilitation programs, on the diminished responsibility of minors, etc.). These results support the desirability of juvenile delinquents are preferably processed in the framework of the juvenile justice and not in the adult criminal justice.